Theoretical Aspects of Supply Chain Management - Rakovska, Miroslava (Research Papers, 2009)
The concept of supply chain stresses on the inter-firm coordination of activities connected with the production and distribution of products. At the root of this concept lies the idea of the necessity of an integrated material flow in the chain which begins with the sources of supply and ends with the delivery of the products to the end consumers.The theoretical aspects of supply chain management are outlined on the basis of a research of its nature, premises for development, its origin and characteristic features. Two dimensions of the concept are refined, the internal and external ones concerning the organizations and four areas of interaction between the members of the chain are defined - these are the management of the material, information and knowledge flows as well as the management of relationships. It is reasoned that the relationships of cooperation between the members of the supply chain are a prerequisite for the successful management of the material and information flows and the exchange of knowledge in it.